Environmental management accounting: identifying future potentials / Gagaring Pagalung Amiruddin - Amiruddin, Gagaring Pagalung (Faculty of Accountancy, 2016)
This study evaluates the use of environmental management accounting(EMA) in maintaining business processes among industrial companies. EMA is a management tool related to environment accountability. It is utilized to improve the financial and environmental performances of companies to achieve sustainability. This study reviews management accounting literature that has examined industrial environmental pollution. Results show that companies that conduct environmental activities identify the problem associated with the environment as environmental cost. This cost is reported in the environmental cost report, which provides a clear, detailed picture of all environment costs. The environmental cost report assists managers in their decision-making process. Generally, companies do not adhere to environmental accountability. In addition, the environmental cost report of companies cannot separated from their financial statements.